Association of 25-Hydroxyvitamin D status and genetic variation in the vitamin D metabolic pathway with FEV1 in the Framingham Heart Study. Issue 1 (December 2015) - Hansen, JG; Gao, W; Dupuis, J; O'Connor, GT; Tang, W; Kowgier, M; Sood, A; Gharib, SA; Palmer, LJ; Fornage, M; Heckbert, SR; Psaty, BM; et al.
Abstract Background Vitamin D is associated with lung function in cross-sectional studies, and vitamin D inadequacy is hypothesized to play a role in the pathogenesis of chronic obstructive pulmonary disease. Further data are needed to clarify the relation between vitamin D status, genetic variation in vitamin D metabolic genes, and cross-sectional and longitudinal changes in lung function in healthy adults. Methods We estimated the association between serum 25-hydroxyvitamin D [25(OH)D] and cross-sectional forced expiratory volume in the first second (FEV1 ) in Framingham Heart Study (FHS) Offspring and Third Generation participants and the association between serum 25(OH)D and longitudinal change in FEV1 in Third Generation participants using linear mixed-effects models. Using a gene-based approach, we investigated the association between 241 SNPs in 6 select vitamin D metabolic genes in relation to longitudinal change in FEV1 in Offspring participants and pursued replication of these findings in a meta-analyzed set of 4 independent cohorts. Results We found a positive cross-sectional association between 25(OH)D and FEV1 in FHS Offspring and Third Generation participants (P  = 0.004). There was little or no association between 25(OH)D and longitudinal change in FEV1 in Third Generation participants (P  = 0.97). In Offspring participants, theCYP2R1 gene, hypothesized to influence usual serum 25(OH)D status, was associated with longitudinal change in FEV1 (gene-basedP  < 0.05). The most significantly associated SNP fromCYP2R1 had a consistent direction of association with FEV1 in the meta-analyzed set of replication cohorts, but the association did not reach statistical significance thresholds (P  = 0.09). Conclusions Serum 25(OH)D status was associated with cross-sectional FEV1, but not longitudinal change in FEV1 . The inconsistent associations may be driven by differences in the groups studied.CYP2R1 demonstrated a gene-based association with longitudinal change in FEV1 and is a promising candidate gene for further studies.